Upaya Meningkatkan Kemampuan Mengenal Angka Menggunakan Media Kartu Angka Bergambar pada Kelompok B Di PAUD Tunas Bangsa Wanareja - Indriyanti, Wiwin; Oktaviana, Winda; Yana, Triyana (Universitas Muhammadiyah Gresik, 2024)
This research explores creative methods to introduce numbers through fun activities for children using illustrated number cards as a learning tool. Research in class B at PAUD Tunas Bangsa Wanareja was carried out due to the lack of ability of young children in understanding numbers 1 to 10. To help them, picture number cards were used as a learning tool adapted to facilitate number recognition. Card shapes that are easy for children to understand, as well as variations in color and images, aim to motivate children's understanding of numbers. This observation aims to increase children's interest in learning mathematics from an early age by utilizing a game-based and interactive approach. The research results illustrate that the use of number card image media improves number recognition skills by arranging numbers 1 to 10 and can stimulate children's cognitive development in the number learning process, creating a positive and enjoyable environment at preschool age compared to conventional learning processes. The practical implication of the observations made is the importance of using interesting and picture-based learning aids to improve the academic achievement of young children in terms of learning basic mathematical concepts such as recognizing numbers